Probability, reliability and statistical methods in engineering design - Haldar, Achintya; Mahadevan, Sankaran (New York ; Chichester : John Wiley and Sons, 2000)
Basic concept of reliability. Mathematics of probability. Modeling of probability. Modeling of uncertainty. Commonly used probability distributions. Determination of distributions and parameters from observed data. Randomness in response variables. Fundamentals of reliability analysis. Advanced topics on reliability analysis...
Keywords: Engineering design; Statistical methods; Reliability (Engineering) -- Statistical methods; Engineering design -- Statistical methods